Implementasi Machine Learning Dengan Metode Text Mining Pada Twitter - Sulaiman, Hamdun; Ryansyah, Muhamad; Widianto, Kudiantoro; Sidik, Sidik; Nugraha, Andria (Fakultas Teknik Universitas Hamzanwadi, 2024)
Currently PT. Telkom Indonesia (Indihome), uses the role of social media as a form of concern for its customers to handle complaints. Tweets from indihome customers on social media twitter are handled by the customer service division of Indihome. The manual of the categorization process carried out by the customer service division of Indihome on every narration of the